Campaspe talks back women who made a difference in early modern art - Deinsen, Lieke van 1987-; Schepers, Bert 1977-; Sterckx, Marjan 1978-; Vlieghe, Hans 1939-; Watteeuw, Bert (Brepols, 2024)
"With forty-three contributions this book pays homage to Katlijne Van der Stighelen, who has shown exceptional range in her own contributions to the history of art in the Southern Netherlands and beyond. With monographs on Peter Paul Rubens and Anthony van Dyck, she has considerably expanded scholarship on canonical artists. Yet early on, a catalogue raisonné of the portraits of the lesser-known Cornelis de Vos revealed that Van der Stighelen was not one to preserve the status quo but to challenge it. Mindful of protagonists and their historiographical pull, she has consistently rehabilitated artists relegated to the background, in some cases by single-handedly saving them from total oblivion and – remarkable feat – having them added to the canon. Portraiture, supposedly a sijd-wegh der consten, was paved into a central avenue of inquiry in Van der Stighelen’s work. Her approach to the genre made it into a pathway for the introduction of women artists. What was a sijd-wegh became a zij-weg. From seminal publications on Anna-Maria van Schurman to revelatory exhibitions on Michaelina Wautier, Van der Stighelen’s particular brand of feminism has impacted scholarship as deeply as it has touched the museum-going public. Women and portraiture are the core themes of the essays assembled in this book. The resulting group portrait is crowded and rambunctious and reflects the varied subject matter that has attracted Van der Stighelen’s professional attention. It also paints a partial portrait of the community of scholars that she has so generously fostered. In trying to summarize the motivations of authors to contribute to this volume or the gratitude of generations of art historians trained by her, it is best to quote the title of the first exhibition on women artists in Belgium and The Netherlands, which Van der Stighelen curated in 1999: Elck zijn waerom."
Auf der Rückseite des Titelblatts: "Essays in honour of Katlijne van der Stighelen"
Bibliographie Katlijne van der Stighelen: Seite 416-428
Keywords: Stighelen, Katlijne van der -- 1959-; Geschichte 1500-1700; Künstlerin; Frauenbild; Kunst; Frau -- Motiv; Frau; Flandern; Niederlande; Stighelen, Katlijne van der; Van der Stighelen, Katlijne - (1959-....); Portrait painting / History; Women in art; Women artists; Festschrift; Aufsatzsammlung